Pembiayaan Mudharabah, Musyarakah Dan Non Performing Financing Terhadap Return On Asset Pada Bank Umum Syariah - Imeh Siti Fatimah; Nana Diana (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2021)
This study aims to determine the relationship between mudharabah, musharaka financing and NPF on ROA in Sharia Commercial Banks registered at Bank Indonesia period 2011-2018. The method used is descriptive verification with a quantitative approach that is through the classic assumption test, multiple linear regression analysis, and hypothesis testing using the T-test, F-test and the coefficient of determination (R2) test. Testing data is processed by using SPSS 22 software. While the data used are secondary data with quantitative data types. The population of this study is 14 Sharia Commercial Banks with a sampling method that is purposive sampling, so that the number of observations obtained is 4 Sharia Commercial Banks. Based on the results of the T-test, mudharabah financing has a positive effect on ROA. Musharaka financing has a negative effect on ROA, and NPF has a negative effect on ROA. Simultaneously all independent variable influences the dependent variable. While the results of the R2 indicate that ROA is influenced by mudharabah, musharaka and NPF financing by 52.3% and the remaining 47.7% is influenced by other variables outside the study.